Pengaruh Penambahan Ekstrak Lemon (Citrus limon) terhadap Karakteristik Minuman Bunga Telang (Clitoria ternatea) - Cahyaning Rini Utami; Sinta Hikmatul Fauziah (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
With its distinctive flower color, the butterfly pea flower has excellent potential as a functional beverage ingredient. Its anthocyanin content provides natural color and high antioxidant activity. This study aims to improve the quality of butterfly pea flower drink by adding lemon extract, which is rich in vitamin C. Using a Completely Randomized Design (CRD) with five treatment levels (10%, 20%, 30%, 40%, and 50% lemon extract), this study evaluated the effect of adding lemon extract on the physicochemical and organoleptic characteristics of butterfly pea flower drink. Antioxidant, pH, color, and sensory evaluations of taste, color, and scent were all included in the analysis. The outcomes demonstrated that adding lemon extract considerably impacted the butterfly pea flower drink's qualities. The best treatment was obtained at a concentration of 10% lemon extract (L1) with an antioxidant value of 0.28 ppm, pH 2.78, L*a*b* color value of 37.87, and received a good assessment in the organoleptic test, namely taste 3.48 (like), color 2.92 (like), and aroma 2.92 (like). * The combination of the natural blue color of butterfly pea flowers with the acidity of lemon produces a drink with an attractive appearance and fresh taste. In addition, adding lemon extract to butterfly pea flower drinks can improve product quality, especially at a concentration of 10%. With the addition of lemon extract, Butterfly pea flower drinks have great potential as functional drinks that are healthy and attractive to consumers.